White burgers, Black cash : fast food from Black exclusion to exploitation - Kwate, Naa Oyo A. (University of Minnesota Press, 2023)
"White Burgers, Black Cash traces the evolution in fast food from the early 1900s to the present, from its long history of racist exclusion to its current damaging embrace of urban Black communities. Deeply researched, compellingly told, and brimming with surprising details, this book reveals the inequalities embedded in America's popular national food tradition"--